2024
DOI: 10.2147/tacg.s437484
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Burden in Greenland of Gastrointestinal Symptoms in Adults with Inherited Loss of Sucrase-Isomaltase Function

Kristine Andersen,
Torben Hansen,
Marit Jørgensen
et al.

Abstract: Background Congenital sucrase isomaltase deficiency (CSID) is in general a very rare disease. However, 2–3% of the Greenlandic population are homozygous (HO) carriers of an Arctic-specific loss-of-function (LoF) variant in the sucrase-isomaltase (SI) encoding gene, causing CSID. The condition is characterized by gastrointestinal symptoms such as stomachache, diarrhea, and weight loss when consuming sucrose, the most common dietary sugar. However, the awareness of the condition in the population an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It could have been interesting to compare the participants with those who did not participate to investigate potential participation bias, i.e. if participants had more symptoms than non-participants or to track their hospital contacts as other studies have done [ 1 , 4 ] this was outside the scope of this qualitative study and not possible due to the participants general rights of data protection [ 35 ]. It could also be a limitation that all participants were selected from former national health survey, and therefore might have positive attitudes to participating in health research generally.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could have been interesting to compare the participants with those who did not participate to investigate potential participation bias, i.e. if participants had more symptoms than non-participants or to track their hospital contacts as other studies have done [ 1 , 4 ] this was outside the scope of this qualitative study and not possible due to the participants general rights of data protection [ 35 ]. It could also be a limitation that all participants were selected from former national health survey, and therefore might have positive attitudes to participating in health research generally.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…symptoms similar to irritable bowel syndrome (IBS) [ 10 ]. This is most likely explaining, why Greenlandic homozygous SI carriers have more gastrointestinal-related health-care contacts and diagnostic procedures compared to other individuals in Greenland [ 1 , 3 , 4 , 10 ]. Further, international research has identified that of people with IBS, sucrose intolerance was present in 35% of patients, and 64% had diarrhoea, and 45% had abdominal pain [ 10 ].…”
Section: Introductionmentioning
confidence: 99%